Optimization of structure of sorting vibratory separators - Shenbor, Vladyslav; Korendiy, Vitaliy; Brusentsov, Volodymyr (Lviv Politechnic Publishing House, 2017)
The problem of substantiation of operational efficiency of vibratory separators designed on the basis of vibratory hopper feeders with electromagnetic vibrations exciters and with conic working bowls is considered in the article. The complex of factors influencing the accuracy and productiveness of separation of coins and disk-shaped products on two or more fractions is overviewed. New models of structures for the effective solution of separation problems are proposed. The design of a highly-efficient and high-performance separator with independent oscillations disturbance is described. The results of experimental investigations of vibratory transportation in elliptical modes of vibrations and of the study of separation efficiency are presented. The recommendations that developers and researchers of such devices may use are given.
Keywords: vibratory separator; sorting; electromagnetic exciter; optimization; bowl; independent disturbance; oscillations; efficiency